Analysis of Tooth Surface Friction Work of Aviation Involute Spline Pair - Chen Yuan; Zhu Rupeng; Jin Guanghu (Jixie chuandong)
Based on finite element method,the aviation involute spline pair model is built,the numerical calculation of the tooth surface friction work of the spline pair tooth surface contact. The influence of the axis deviation on main parameters of involute spline pair is analyzed,the changes law of the maximum tooth friction work is obtained. The results show that,the friction work will increase with the value of axis deviation increasing,while increment slows down; the friction work will increase with friction coefficient increasing,while increment is comparatively constant. The increment of friction work is significant when pore diameter of external spline is especially large,the friction work goes to besteady when contact length is larger than 0. 45.